Symbiosis of Solar Cell Technology, AI, Business IT, Radio waves, Vaccines, and Antibiotics: A Comprehensive Review for Sustainable Innovation - Abdul Razaq (CV. Shofanah Media Berkah, 2023)
In order to promote sustainable innovation, this review article offers a thorough analysis of the synergistic integration of several technologies, including radio waves, solar cell technology, artificial intelligence (AI), business information technology (IT), vaccinations, and antibiotics. A thorough examination is conducted, emphasizing the ways in which smart technology, healthcare solutions, and renewable energy are intertwined. The abstract explores how technology might improve through the use of solar cells and radio waves, while business IT and artificial intelligence maximize efficiency. Additionally, the assessment looks into how vaccines and antibiotics might improve public health in a revolutionary way. The essay attempts to provide insights into the comprehensive and sustainable approach that arises when multiple technologies collide for the benefit of business and society by tying these disciplines together. This analysis delves into the complex relationships that exist between artificial intelligence (AI) and solar cell technology, explaining how the combination of cutting-edge computer power and sustainable energy sources drives previously unheard-of breakthroughs. Business IT becomes a crucial enabler, coordinating the smooth integration of various technologies to maximize productivity and decision-making procedures. The paper also explores the crucial field of medicine, where antibiotics and vaccinations are essential for building resilient communities. This review highlights the need for interdisciplinary collaboration in addressing the difficulties of our fast evolving world, while also elucidating the possibility for holistic and sustainable solutions by bringing these technical and medical developments together.